PENGARUH KELUARGA, SEKOLAH DAN TOKOH ADAT TERHADAP PEMBENTUKAN ORIENTASI POLITIK MASYARAKAT SEDULUR SIKEP DI DESA BATUREJO KECAMATAN SUKOLILO KABUPATEN PATI - YENI AGUSTINA; SUSILO UTOMO; YUWANTO . (Journal of Politic and Government Studies, 2016)
This research arranged to understand about influence of family, school, and communityfigure to forming of political orientation in Sedulur Sikep Community. Trough politicalsocialization, people developing attitude and orientation to political life which take place in thesociety. In this research, the most influental political socialization’s agents in the traditionalcommunity are family, school, and community figure. This research using quantitativeapproachwith explanatory research type. Data gathered from questionnaire which population are SedulurSikep community in Baturejo Vilage,Pati District, with number 1050person. Scale that used areordinal scale. Respondent choosen by Multistage Random Sampling technique, the result is 64respondent. Then, in the data analisis will using software SPSS 16.0.The result of the research are, family, school, and community figure have influence toforming of political orientation in Sedulur Sikep community inBaturejo Village, Pati district.Family(X1) with political organization (Y)have strong relationship with efeciency correlation0,624; school (X2) with political orientation (Y)have relatively strong relationship withefeciencycorrelation 0,466; community figure (X3) with political orientation (Y)have relativelystrongrelationship with eficiency correlation 0,466;and family, school, and community figuretogetherhave influence with the forming of political orientation in Sedulur Sikep community Keyword = Influence, Political Socialization, Political Orientation.